Addressing Diagnostic and Therapeutic Challenges in a Case of Concurrent Tinea and Plaque Psoriasis - Asnani, Divya; Singh, Shrishti; Gupta, Aayush (Case reports in dermatology, 2024)
Abstract Introduction: The annular lesions of dermatophytosis can closely resemble the plaques of psoriasis, posing significant diagnostic and treatment challenges. Methotrexate, a common treatment for psoriasis, can exacerbate the former due to its immunosuppressive effects. Case Report: ​​A middle-aged man with chronic plaque psoriasis was on tablet methotrexate (7.5 mg once weekly) and topical steroids for 1 year. Despite some improvement, new annular lesions emerged whenever topical steroids were tapered. Frustrated with the lack of disease control, the patient finally visited a tertiary care center, where tinea corporis was diagnosed alongside psoriasis via dermoscopy, mycological tests, and histopathology. Methotrexate and steroids were discontinued, and the patient was started on antifungals. Once the dermatophytosis was brought under control, methotrexate was resumed alongside targeted application of steroid and antifungal creams. Conclusion: The coexistence of tinea corporis and psoriasis can be challenging to diagnose and treat, necessitating thorough clinical evaluation and mycological testing. Proactive monitoring and timely intervention are crucial to prevent complications and ensure optimal management outcomes in immunosuppressed individuals with dermatophyte infections. Introduction: The annular lesions of dermatophytosis can closely resemble the plaques of psoriasis, posing significant diagnostic and treatment challenges. Methotrexate, a common treatment for psoriasis, can exacerbate the former due to its immunosuppressive effects. Case Report: ​​A middle-aged man with chronic plaque psoriasis was on tablet methotrexate (7.5 mg once weekly) and topical steroids for 1 year. Despite some improvement, new annular lesions emerged whenever topical steroids were tapered. Frustrated with the lack of disease control, the patient finally visited a tertiary care center, where tinea corporis was diagnosed alongside psoriasis via dermoscopy, mycological tests, and histopathology. Methotrexate and steroids were discontinued, and the patient was started on antifungals. Once the dermatophytosis was brought under control, methotrexate was resumed alongside targeted application of steroid and antifungal creams. Conclusion: The coexistence of tinea corporis and psoriasis can be challenging to diagnose and treat, necessitating thorough clinical evaluation and mycological testing. Proactive monitoring and timely intervention are crucial to prevent complications and ensure optimal management outcomes in immunosuppressed individuals with dermatophyte infections. Introduction: The annular lesions of dermatophytosis can closely resemble the plaques of psoriasis, posing significant diagnostic and treatment challenges. Methotrexate, a common treatment for psoriasis, can exacerbate the former due to its immunosuppressive effects. Case Report: ​​A middle-aged man with chronic plaque psoriasis was on tablet methotrexate (7.5 mg once weekly) and topical steroids for 1 year. Despite some improvement, new annular lesions emerged whenever topical steroids were tapered. Frustrated with the lack of disease control, the patient finally visited a tertiary care center, where tinea corporis was diagnosed alongside psoriasis via dermoscopy, mycological tests, and histopathology. Methotrexate and steroids were discontinued, and the patient was started on antifungals. Once the dermatophytosis was brought under control, methotrexate was resumed alongside targeted application of steroid and antifungal creams. Conclusion: The coexistence of tinea corporis and psoriasis can be challenging to diagnose and treat, necessitating thorough clinical evaluation and mycological testing. Proactive monitoring and timely intervention are crucial to prevent complications and ensure optimal management outcomes in immunosuppressed individuals with dermatophyte infections. Introduction: The annular lesions of dermatophytosis can closely resemble the plaques of psoriasis, posing significant diagnostic and treatment challenges. Methotrexate, a common treatment for psoriasis, can exacerbate the former due to its immunosuppressive effects. Case Report: ​​A middle-aged man with chronic plaque psoriasis was on tablet methotrexate (7.5 mg once weekly) and topical steroids for 1 year. Despite some improvement, new annular lesions emerged whenever topical steroids were tapered. Frustrated with the lack of disease control, the patient finally visited a tertiary care center, where tinea corporis was diagnosed alongside psoriasis via dermoscopy, mycological tests, and histopathology. Methotrexate and steroids were discontinued, and the patient was started on antifungals. Once the dermatophytosis was brought under control, methotrexate was resumed alongside targeted application of steroid and antifungal creams. Conclusion: The coexistence of tinea corporis and psoriasis can be challenging to diagnose and treat, necessitating thorough clinical evaluation and mycological testing. Proactive monitoring and timely intervention are crucial to prevent complications and ensure optimal management outcomes in immunosuppressed individuals with dermatophyte infections.